Integrating and combining grammar translation teaching methods with biography driven instruction in China: a qualitative case study - Han, Chen (Kansas State University, 2023)
Language is a communication tool used by everyone in their daily life as a means to convey information and arguments to others. Even though the Ministry of Education (MoE) in China has been switching from exam-oriented education to cross-cultural communication education, the classroom practices, teaching methods, evaluation system, school structures and materials, and aspects of the administrators and teachers are still traditional and contrary to the principles of cross-cultural communication and exchange. This study offered a biography-driven instruction (BDI) approach as a new method in teaching English as a Foreign Language (EFL) in China and examined two EFL teachers as they navigated the conceptual, pedagogical, structural, and political dilemmas of implementing a BDI approach in a Grammar Translation Method (GTM) context. Professional development about BDI, including coaching sessions, was provided to two EFL teachers working in two public junior high schools in the province of Shaanxi and Gansu, and the understanding of the BDI approaches on teachers’ practice and implementation was analyzed. Different types of data sources, such as in-depth interviews of participants, pre- and post- surveys, and lesson plans and artifacts were collected and analyzed to better understand how these teachers made meaningful use of this new approach and negotiated its use in a GTM- dominate context. The findings, in general, showed that the BDI approaches helped these teachers build a more constructivist classroom while combining GTM and BDI methods, views, and classroom applications. This study provided findings regarding exploration, integration, and localization of a BDI approach in the context of GTM. Well-planned and well-organized teacher development with on- going support and counseling is necessary. Further, professional development and coaching conversations have important roles in teacher development. This study also revealed that the teachers were the most important people in implementing a new educational approach and shift in teaching methods as required by the MoE to ensure they can reach a more communicative and constructivist classroom, regardless of any insufficiencies.
Keywords: Biography-driven instruction; Grammar-translation method; Professional developmentCommunicative approach